Pengaruh Keberadaan Pertambangan PT. IWIP Terhadap Masyarakat di Provinsi Maluku Utara Berdasarkan Perspektif Hukum Lingkungan (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
The preparation of this scientific paper aims to analyze economic, social, environmental, and ecological issues that arise as a result of the interaction between mining activities and the existence of natural resources. This study employs a normative legal research method. Based on the findings, the mining activities of PT. IWIP in North Maluku Province have positive impacts that can support economic development. However, the adverse effects on the environment tend to be more significant. This is evidenced by water, air, and soil pollution caused by PT. IWIP’s mining operations in Central Halmahera Regency. According to the author, this is a very serious issue. The government’s ambition to make Indonesia a leading producer of nickel-based products has endangered the lives of residents in Central Halmahera living near nickel mining areas. These communities are forced to sacrifice their livelihoods, and even their health has been affected. Moreover, there is no accountability from PT. Indonesia Weda Bay Industrial Park regarding the environmental impacts, which are influenced by the new regulations that have been enacted. Article 88 of Law Number 6 of 2023, which ratifies Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation, removes the provision that previously did not require proof of fault. This change makes it more difficult for affected communities to prove the environmental pollution that has occurred.